Contribution of village community banks in household rice production: A case of Morogoro district - LadoHaule, Alice (Mzumbe University, 2024)
A dissertation submitted to the Institute of Development Studies in partial fulfillment of the requirements for award of the Master of Science in Development Policy (MSc. DP) Degree of Mzumbe University